Aktualisasi Model Pembinaan Karakter Komunitas Anak Jalanan - Julaeha, Siti; Muslim, Erwin; Ahmad, Nurwadjah; Suhartini, Andewi (Ikatan Da'i Indonesia, 2023)
This study tries to unravel the problems of street children related to character building, especially in the aspects of personal and social skills. So we need a model of character education that is considered suitable to be implemented in street children. This study uses a qualitative approach with library research methods. The results of this study conclude that, Among the character education models that can be implemented on street children are problem-based learning models, emphasizing more on the application of problem solving methods or problem solving which by John Dewey consists of six learning steps as follows: 1) formulating problems; 2) analyze the problem; 3) formulate hypotheses; 4) collect data; 5) hypothesis testing; and 6) formulate problem solving recommendations.